Some questions of Islamic banking - Ligeti, Sándor (Acta Scientiarum Socialium, 2011)
Some Questions of Islamic Banking Islamic banking is considerably different from conventional banking system since the Muslim religion forbids giving or receiving interest. The competition with conventional banks forced Islamic banks introduce new products and institutions such as Islamic bonds, structured products and mutual funds based on traditional Islamic financial products. They replicate short selling as well. These products and institutions indicate debates among Islamic scholars, law schools in different Muslim countries whether they are acceptable on the basis of the Sharia or not. Liquidity management is easier in Islamic banks be-cause of their main source of liquidity is costumer deposits and their leverage is lower than in conventional banks. Their disadvantage is the lack of the limited role of interbank market and the lender of last resort of central banks. Global financial crisis impacted Islamic banks less than the conventional banks because the profit and loss sharing system, the lower leverage and the prohibition of speculation. The recent policy changes in Muslim world can boost the spread of Islamic banking.
Keywords: Islamic banking; securities; liquidity; financial crisis